Local Wisdom Based Religious Counseling to Reduce Student Bullying Behavior - Abdul Munir (Britain International for Academic Research (BIAR) Publisher, 2026)
The purpose of this study is related to religion counseling based on local wisdom in reducing student bullying behavior. Religion and local wisdom are important elements that have the potential to be implemented in counseling. Religious values ​​and local wisdom are expected to increase the effectiveness of the counseling process. Religious values ​​and local wisdom can be elements that support the client's acceptance of counseling interventions, so that the counseling process will be meaningful for the client. According to Rangks (2016), counseling with religious values ​​combined with local wisdom has proven effective when implemented to overcome problems experienced by individuals. This study uses research and development (R&D). The development model used is the ADDIE Model (analyze, design, development, implementation, evaluation). The development results were validated by two counseling experts to obtain a feasibility test (validation) and reliability of the local wisdom-based religious counseling model. Next, a limited trial was conducted through an experiment with 10 (ten) students who were perpetrators of bullying. The instruments used were an expert validation sheet, a questionnaire about bullying behavior, and a questionnaire of students' responses to the local wisdom-based religious counseling they received. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results of the validation test by two (2) counseling experts were categorized as good (75%). Notes and suggestions for improvement included emphasizing the religious and local wisdom aspects more and telling more folktales related to friendship. Based on input and comments from these two counseling experts, the local wisdom-based religious counseling model underwent revision stage I. The implementation stage will end with an evaluation, namely revision stage II. Based on the experimental test data on students who were bullies, a reduction in bullying behavior was obtained with a difference in pretest and posttest scores of 52%. Then tested using the Wilcoxon test, a significant value of 0.005 was obtained, which is smaller than 0.05, meaning that there is a significant difference between the pretest and posttest scores. Students' responses to the local wisdom-based religious counseling they participated in were generally categorized as feeling happy, interesting, clear, and easy to understand. Overall, it can be concluded that the local wisdom-based religious counseling model developed is able to reduce student bullying behavior.